Large‐scale pedigree analysis leads to evidence for founder effects of hypertrophic cardiomyopathy in rhesus macaques (Macaca mulatta). Issue 4 (9th May 2014) - Kanthaswamy, Sree; Reader, Rachel; Tarara, Ross; Oslund, Karen; Allen, Mark; Ng, Jillian; Grinberg, Chloe; Hyde, Dallas; Smith, David G.; Lerche, Nicholas
Abstract Background Hypertrophic cardiomyopathy (HCM) is the abnormal thickening of the ventricles and an increase in cardiac mass. Methods Pedigree analyses involving 108 rhesus macaques with pronounced HCM were performed. Results Analyses revealed a strong genetic predisposition to this disease. Conclusions Macaques are ideal for investigating HCM because of their marked similarity to humans genetically, physiologically, and anatomically.